Hydrothermal alkali pretreatment contributes to fermentative methane production of a typical lipid from food waste through co-production of hydrogen with methane. (June 2020) - Cheng, Jun; Yue, Liangchen; Hua, Junjie; Dong, Haiquan; Zhou, Junhu; Li, Yu-You
Graphical abstract: Highlights: Glycerol trioleate as typical lipid from waste was pretreated by hydrothermal alkali. Hydrolysis and degradation effect were stronger with higher hydrothermal temperature. Hydrothermal alkali (220 °C) led to the highest H2 and CH4 yields. The coating of microorganisms by lipids was relieved by hydrothermal pretreatment. Abstract: In order to relieve the suppression problems of methanogenesis with microorganisms surrounded by undegraded lipids in food waste, hydrothermal alkali pretreatment was utilized to degrade lipids for promoted methane production through the co-production process of hydrogen with methane. GC–MS results demonstrated that oleic acids and hexadecanoic acids derived from degraded glycerol trioleate increased (from 43.29% to 58.22%, and from 1.06% to 8.25%, respectively) when the pretreatment temperature was increased from 160 °C to 220 °C. SEM, TEM and FTIR analyses showed that the pre-treatment at 220 °C effectively degraded 87.56% of glycerol trioleate and drastically relieved the covering of methanogens by non-degraded lipids. The methane yield and the production peak rate of glycerol trioleate also increased (from 636.85 to 877.47 mL CH4 /g-total volatile solid (VS), and from 32.60 to 51.22 mL CH4 /g-VS/d, respectively), which led to an increased energy conversion efficiency from 48.05% to 66.21% through the co-production of hydrogen with methane.